Calpain-mediated cleavage of mitochondrial fusion/fission proteins in acetaminophen-induced mice liver injury. (6th June 2022) - Shan, Shulin; Liu, Zhaoxiong; Li, Linlin; Zhang, Cuiqin; Kou, Ruirui; Song, Fuyong
Mitochondrial dysfunction was considered to be a critical event in acetaminophen (APAP) -induced hepatotoxicity. Recent studies suggest that abnormal mitochondrial dynamics contributes to mitochondrial dysfunction in APAP-induced liver injury, yet the underlying mechanisms responsible for deregulated mitochondrial dynamics remains elusive. In this study, C57BL/6 mice were used to establish a model of acute liver injury via intraperitoneal (i.p.) injection with overdose of APAP. Furthermore, calpain intervention experiments were achieved by the inhibitors ALLN or calpeptin. The activity of serum enzymes and pathological changes of APAP-treated mice were evaluated, and the critical molecules in mitochondrial dynamics and calpain degradative pathway were determined by electron microscopy, immunoblot and calpain activity kit. The results demonstrated that APAP overdose resulted in a severe liver injury, mitochondrial damage and an obvious cleavage of fusion/fission proteins. Meanwhile, the activation of calpain degradative machinery in liver were observed following APAP. By contrast, pretreatment of calpain inhibitors significantly inhibited the activation of calpains. Our further investigation found that ALLN or calpeptin administration significantly suppresses the changes of mitochondrial dynamics in APAP-treated mice and finally protected against APAP-induced hepatoxicity. Overall, these results suggest that calpain-mediated cleavage of mitochondrial dynamics proteins was involved in the pathogenic process of mitochondrial dysfunction and thus present a potential molecular coupling APAP-induced hepatotoxicity.